Pengaruh Digital Tax Administration Terhadap Kepatuhan Wajib Pajak (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Increasing taxpayer compliance is one of the government's main focuses in optimizing state revenue. This study aims to analyze the effect of Digital Tax Administration on taxpayer compliance. The research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 100 individual taxpayers who had utilized digital tax services, including e-Registration, e-Filing, e-Billing, and e-Faktur. The data were analyzed using descriptive statistics, validity and reliability tests, and simple linear regression analysis. The results indicate that Digital Tax Administration has a positive and significant effect on taxpayer compliance, as evidenced by a regression coefficient of 0.678 and a significance value of 0.000, which is lower than 0.05. Furthermore, the coefficient of determination (R²) of 0.562 indicates that 56.2% of the variation in taxpayer compliance can be explained by Digital Tax Administration. These findings suggest that the implementation of digital tax services enhances taxpayer compliance by improving efficiency, accessibility, and convenience in fulfilling tax obligations. Therefore, strengthening digital tax administration can be considered an effective strategy to support tax reform and optimize state revenue.